Perspectives of people with dementia and family caregivers about dementia clinical research: Health services research / Services. (7th December 2020) - Bouranis, Nicole; Gelmon, Sherril B; Lindauer, Allison; Waddell, Elizabeth N; Richardson, Dawn M; Woo, Hyeyoung
Abstract: Background: The National Institute on Aging's (NIA) national strategy to increase ADRD clinical research participation recommends continued research on identifying barriers and facilitators for ADRD study recruitment. This study builds upon its work by identifying factors affecting dementia research participation according to people with ADRD and their family caregivers in Portland, Oregon. Method: A community advisory board (CAB) comprised of clinicians, researchers, advocates, people with dementia, family caregivers, and older African Americans was established for this project. Semi‐structured dyadic interviews were conducted with individuals living with MCI or ADRD and their family caregivers, half of whom had participated in ADRD clinical research. Dyad members were interviewed separately. Interviews were audio‐recorded, coded and analyzed through thematic analysis where themes emerged from the data organically. The investigator was the single coder; the CAB interpreted findings by identifying what was most important, surprising, or missing from the interviews. Result: There is a lack of knowledge about opportunities in the Portland area. Many interviewees were unaware of dementia studies, which was surprising as many interviewees were recruited from organizations with rich knowledge of research opportunities. One's perceived value of ADRD research did not increase their likelihood of joining a study. Many caregivers either do not have or did not want to use limited free time to be a study partner; however, several caregivers noted that they would participate in the study if provided some sort of caregiver benefit to ease their burden, such as support, education, or respite. The number of people who avoid research because it involves taking study drugs was substantial among interviewees. Conclusion: Several recommendations can be made based on this study. Researchers can partner with other healthcare and ADRD resource providers to share study opportunities. Study partners should be recognized as full participants who deserve compensation for their time and effort. Research organizations could develop strategies to remove or reduce the time spent and distance traveled in order to participate in research. Researchers could highlight the benefits of helping others by partnering with people with ADRD and caregivers to share the experience of participating in research.